Airship Technology - Navarrete, Jazmyn, author 646397 (Delhi, India : White Word Publications, 2012)
A propeller is a type of fan that transmits power by converting rotational motion into thrust . A pressure difference is produced between the forward and rear surfaces of the airfoil-shaped blade, and air or water is accelerated behind the blade. Propeller dynamics the four engine as part of can be modeled by both Bernoulli's principle and Newton's third law. A propeller is often colloquially known as screw both in aviation and maritime.